Maternal, Democratic, and Situational Leadership: A Case Study of Women Principals in Pekanbaru Public High Schools - Herlina Permata Sari; Aan Komariah; Asep Suryana; Yayah Rahyasih (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates women's leadership models and their role in enhancing the quality of education at SMA Negeri 16 and SMA Negeri 18 in Pekanbaru City. Drawing on the concept of maternal leadership, the research aims to understand how female principals shape school culture and instructional practices. A qualitative case study approach was employed, focusing on two public high schools. Data were collected through semi-structured interviews, participatory observations, and document analysis, with thematic coding facilitated by NVivo 12. Findings reveal that women leaders at both institutions exhibit humanistic, participatory, communicative, and maternal leadership characteristics. Maternal traits such as empathy, emotional closeness, and care for both teachers and students foster a harmonious and supportive school climate. At SMA Negeri 16, leadership emphasizes discipline and governance consistency, while at SMA Negeri 18, the focus is on innovation, collaboration, and empowerment. Key strategies across both schools include teacher motivation, intensive communication, reflective practices, and continuous quality improvement through a humanist approach. This study contributes to the growing discourse on gender and leadership in education by highlighting the effectiveness of maternal leadership styles in fostering inclusive, collaborative, and high-performing school environments. The findings suggest that such models hold significant promise for improving educational quality through relational and transformative leadership practices.